2002
DOI: 10.2135/cropsci2002.1900
|View full text |Cite
|
Sign up to set email alerts
|

Freeze Tolerance of Seed‐Producing Turf Bermudagrasses

Abstract: Bermudagrass, Cynodon dactylon (L.) Pers., suffers periodic severe winter-kill throughout much of its area of use in the contiguous USA. A research goal is to increase freeze tolerance in cultivars to lessen the risk of such damage. An identified research need is for Cynodon germplasm resources to be characterized for freeze tolerance and hybridization potential. Accordingly, the objective of this research was to characterize the relative freeze tolerance of selected fertile bermudagrass plants. Nine tetraploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The data observed from a freeze tolerance study of fertile turf‐type C. dactylon var. dactylon (Anderson and Taliaferro, 2002) showed that there was a significant correlation between freeze‐tolerance value and average annual temperatures at the geographic origins of the bermudagrasses. Harlan et al.…”
Section: Resultsmentioning
confidence: 99%
“…The data observed from a freeze tolerance study of fertile turf‐type C. dactylon var. dactylon (Anderson and Taliaferro, 2002) showed that there was a significant correlation between freeze‐tolerance value and average annual temperatures at the geographic origins of the bermudagrasses. Harlan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature (LT) is one of the most important abiotic stress factors affecting plant survival and growth, and it is also the main factor that determines the geographical distribution and growth season of plants [1]. Cold resistance is a complex feature and can be a major influence on plant survival [2].…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature (LT) is a major determinant that limits the geographical distribution and growing season of plants [1]. Overwintering plants may increase their cold tolerance when exposed to low temperatures.…”
Section: Introductionmentioning
confidence: 99%